Autonomous driving: are we ready to accept it? A study about information influences on technology acceptance - Nóbrega, Patrícia Pestana (2021)
In this era of technology we live in, transportation is the subject of rapid developments with brands racing, with a focus on becoming the pioneer in launching a stand-alone car. The planned dates for public release are close, however today there are only prototypes in test with level of automation 4. Being a recent subject, little information exists for both consumers or companies, so the study proposes to identify the information and technology that can influence opinion on these cars. The Innovation Adoption in Robotics (IAR) model was selected as the study’s theorical reference to study the intention of adopting autonomous vehicles, to determine the variables and construct a questionnaire to collect opinions and quantify other variables related to car acceptance. This model is based on the Technology Acceptance Model (TAM), developed by Davis (1989) and the Diffusion of Innovations Model (DIM) developed by Rogers' (1983). It is noted through the study that the subject is known the inquirers, although information about it is scarce, being evoked by them the need to obtain further progress in technology, to experiment and to obtain more information. Only by mitigating the abovementioned faults, uncertainties as to the reliability of the system and the advantages could be better clarified. Absence of information currently available about this technology and uncertainties regarding price, preparation of countries’ preparation and of the population itself, together with the impossibility of experiencing the car make these technology’s acceptance difficult.